2023
DOI: 10.15561/26649837.2023.0309
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the relationship between isokinetic lower extremity strength and the vertical jump parameter in elite women football players

Mehmet Soyal,
Ömer Aksoy,
Onur Şengöl
et al.

Abstract: Background and Study Aim.  It can be said that recently, with the popularity of women's football and playing at a professional level, physical and physiological needs have increased. In this context, this study was conducted to examine the relationship between isokinetic lower extremity strength and vertical jump parameters in elite female football players. Material and Methods. The model of the research was the relational survey model, one of the survey models. The research group consisted of 26 volunteer pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Covering large distances during football matches requires a special level of physical fitness from the players to facilitate the numerous accelerations, decelerations, changes of rhythm and direction specific to the game and the current dynamics in professional football (Martín Barrero et al, 2022;Enes et al, 2021;Tuo et al, 2019). The studies revealed the quantitative and qualitative aspects concerning the distances covered by the players corroborated with the other physical, functional, technical and tactical parameters represent important indicators in the efficiency of football training (Morina et al, 2021;Gonçalves et al, 2018;Manescu, 2013;Manolache , 2019;Soyal et al, 2023).…”
Section: Discussionmentioning
confidence: 86%
“…Covering large distances during football matches requires a special level of physical fitness from the players to facilitate the numerous accelerations, decelerations, changes of rhythm and direction specific to the game and the current dynamics in professional football (Martín Barrero et al, 2022;Enes et al, 2021;Tuo et al, 2019). The studies revealed the quantitative and qualitative aspects concerning the distances covered by the players corroborated with the other physical, functional, technical and tactical parameters represent important indicators in the efficiency of football training (Morina et al, 2021;Gonçalves et al, 2018;Manescu, 2013;Manolache , 2019;Soyal et al, 2023).…”
Section: Discussionmentioning
confidence: 86%
“…The technique of the football game consists of sometimes sudden changes of direction, sprints and vertical jumps that involve an eccentric and concentric effort in the muscles of the lower limbs (Buhry et al, 2022. The isokinetic elements in making the vertical jumps, specific to the football game, performed at speed, assume an almost maximum muscle strength, due to the load and the dynamics of the movement Soyal et al, 2023). According to the specialists, the following are involved in the vertical jump: the strength of the leg muscles, the speed of muscle force generation, the speed of contraction, the intramuscular coordination and the efficiency of the muscle stretching-shortening system (Zileli & Söyler, 2021).…”
Section: Introductionmentioning
confidence: 99%